PENGENGEMBANGAN LABORATORIUM BISNIS MELALUI SEGMENTASI, TARGETING DAN POSISIONING - Agus Nopianto; Destina Paningrum (JURNAL EKONOMI BISNIS DAN KEWIRAUSAHAAN, 2014)
Cultivate new entrepreneurs who are well educated and have a mindset to create employment, entrepreneurship is not only defined as business skills. More than thatentrepreneurship is being creative innovative , and pull the trigger. Entrepreneurship can be applied in all areas of work and life, so it is useful as a preparation to the future of the students, if you want a career in any field. Laboratory Business Development aims to become business incubator that accompany the students who are interested in or have previously entrepreneurship.